Novel technique for the calculation of eddy current losses and Lorentz forces in foil winding transformers - Díaz Flórez, Guillermo A. (2017)
This paper presents a new methodology to calculate eddy current losses and Lorentz forces in foil winding transformers. This methodology is based on the equivalent winding current distribution in the foil winding and the iron core obtained by means of the Semianalytic Integral Method (SAIM) [1]. The main advantage of the calculation technique presented in this paper is that it is based on  mathematical expressions which are compact and easy to evaluate, thus achieving a considerable reduction in the overall time required to determine the design parameters of the transformer. The results obtained from the proposed formulation have been compared to those obtained using the finite element method (FEM) using as a case study a 10 MVA transformer and an excellent agreement between both techniques has been obtained.